Wacana Larangan Musik di Medsos: Kontestasi Tafsir Dalil dan Latar Belakang Ideologi Tokoh Dakwah - Kadri, Wahab Nur; Han, Muhammad Ibtisam; Fachruddin, Ahmad (Komsospol, 2024)
This research explores the discourse on the prohibition of music in Islam as discussed on social media, focusing on the contestation of interpretations of religious propositions by missionary figures and their ideological backgrounds. The study employs a qualitative approach, using critical discourse analysis methods to examine the discourse on the prohibition of music within the social media landscape in Indonesia. Data were collected from YouTube and TikTok and analyzed through three stages: micro, meso, and macro. At the micro stage, the analysis centers on linguistic details and text structure, including the choice of words, sentences, and metaphors used to construct arguments for the prohibition of music. At the meso stage, the analysis examines how propositions and arguments are organized and connected to form a coherent discourse. At the macro stage, the discourse is analyzed within a broader social and ideological context, considering the role of social media, religious ideology, and interpretations of religious propositions. Data coding and categorization techniques were employed to identify the main themes, rhetorical strategies, and socio-ideological contexts that shape the discourse on music prohibition, ensuring a systematic and comprehensive analysis. The findings indicate that social media has become an arena for the contestation of religious discourse, where figures with various ideological backgrounds interact and compete to influence public opinion. Interpretations of the law regarding music vary, ranging from a conservative approach that prohibits music outright to a moderate approach that recognizes music's potential for missionary purposes. This research also reveals how social media influences individuals' religious views and practices, with users actively participating in discussions and contributing to the dissemination of discourse.